Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The following differentiated implicitly with respect to $\theta$:

$3x = \tan \, \theta $

The book says

$3 dx = \sec^2 \theta \, d \theta$

One could start the calculation like this (I think):

$ \frac{d}{d \theta}3x = \frac{d}{d \theta} \tan \, \theta $

From there I'm not really sure about the steps.

share|cite|improve this question
The book is wrong, the answer is 3 dx = sec(theta)^2 dtheta. – quanta Apr 19 '11 at 11:02
Sorry, typo. I'll fix. – Algific Apr 19 '11 at 11:07
you can do any of the ways, it gives you the same result. – amul28 Apr 19 '11 at 11:14
up vote 3 down vote accepted

I don't know what you are asking but I will explain how I view this sort of thing.

What is meant by $$3x = \tan(\theta)$$ is that both sides are the same function of $x$ or $\theta$ and $x$ and $\theta$ are related somehow. Writing out the relation explicitly we have $$3x = \tan(\theta(x)).$$ Now define $f(x) = 3x$ and $g(x) = \tan(\theta(x))$, this equation means that $f = g$.

Applying the derivative operator to both sides $f' = g'$ we have $$3 = \theta'(x)\sec(\theta(x))^2$$ (by the chain rule and derivative of tan = sec^2). Now you can write it as a differential $$3 \mathrm{d}x = \sec(\theta(x))^2 \theta'(x) \mathrm{d}x = \sec(\theta)^2 \mathrm{d}\theta$$ since $\theta'(x) \mathrm{d}x = \mathrm{d}\theta$.

share|cite|improve this answer
I just leveled up! Thank you! – Algific Apr 19 '11 at 14:54

This is differential notation. If $y=f(x)$, then it is customary to write $dy=f'(x)dx$. What this says is that a small change in $x$, $dx$, produces an approximate change on $y$ of $f'(x)dx$. In your instance you have $x=f(\theta)$ and so $dx=f'(\theta)d\theta$. The concept comes into play when you talk about linear approximation and you are using the differentials to approximate error. So you have

$$ x=\frac{1}{3}\tan\theta $$

which gives

$$ dx=\frac{1}{3}\sec^2(\theta) d\theta. $$

share|cite|improve this answer

It is simply that $$\frac{d}{d \theta} \left( 3x \right) = \frac{d}{d \theta} \left( \tan \theta \right)$$

Then we know that $$\frac{d}{d \theta } \left( \tan \theta \right) = \mbox{sec}^2 \theta $$


$$\frac{d}{d \theta} \left( 3x \right) = 3 \frac{dx}{d \theta}$$

(Can you see why?)

share|cite|improve this answer
Why is that last part equal to 3 dx? – Algific Apr 19 '11 at 11:31
@Algific If you have a look at quanta's answer - I could really write $3 x(\theta)$. Then it should be clear – Juan S Apr 19 '11 at 11:33

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.